Planning the location of facilities to implement a reverse logistic system of post-consumer packaging using a location mathematical model. Issue 12 (December 2017) - Couto, Maria Claudia Lima; Lange, Liséte Celina; Rosa, Rodrigo de Alvarenga; Couto, Paula Rogeria Lima
The implementation of reverse logistics systems (RLS) for post-consumer products provides environmental and economic benefits, since it increases recycling potential. However, RLS implantation and consolidation still face problems. The main shortcomings are the high costs and the low expectation of broad implementation worldwide. This paper presents two mathematical models to decide the number and the location of screening centers (SCs) and valorization centers (VCs) to implement reverse logistics of post-consumer packages, defining the optimum territorial arrangements (OTAs), allowing the inclusion of small and medium size municipalities. The paper aims to fill a gap in the literature on RLS location facilities that not only aim at revenue optimization, but also the participation of the population, the involvement of pickers and the service universalization. The results showed that implementation of VCs can lead to revenue/cost ratio higher than 100%. The results of this study can supply companies and government agencies with a global view on the parameters that influence RLS sustainability and help them make decisions about the location of these facilities and the best reverse flows with the social inclusion of pickers and serving the population of small and medium-sized municipalities.